2022
DOI: 10.3389/fcimb.2022.906303
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Disordered Microbial Metabolites and Changes of Neurotransmitters in Depressed Mice

Abstract: BackgroundsMany pieces of evidence demonstrated that there were close relationships between gut microbiota and depression. However, the specific molecular mechanisms were still unknown. Here, using targeted metabolomics, this study was conducted to explore the relationships between microbial metabolites in feces and neurotransmitters in prefrontal cortex of depressed mice.MethodsChronic unpredictable mild stress (CUMS) model of depression was built in this study. Targeted liquid chromatography–mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…These metabolites covered two pathways, and perturbations to these pathways have previously been observed in mental health outcomes [ 31 ]. Metabolomic studies have implicated alterations to leucine, tyrosine, and methionine pathways in mental health conditions such as anxiety and depression [ 32 ]. Likewise, our study found evidence that may suggest that higher levels of the leucine metabolite 3-hydroxy-2-ethylpropionate were associated with abnormal scores across all three BSI subscales of interest.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites covered two pathways, and perturbations to these pathways have previously been observed in mental health outcomes [ 31 ]. Metabolomic studies have implicated alterations to leucine, tyrosine, and methionine pathways in mental health conditions such as anxiety and depression [ 32 ]. Likewise, our study found evidence that may suggest that higher levels of the leucine metabolite 3-hydroxy-2-ethylpropionate were associated with abnormal scores across all three BSI subscales of interest.…”
Section: Discussionmentioning
confidence: 99%
“…This was partly explained by the different changes in tryptophan pathway metabolites and neurotransmitters along the gut-brain axis. The relationship between microbial metabolites in feces and neurotransmitters in the prefrontal cortex of depressed mice was also explored using targeted metabolomics [91]. This suggested that the disruption of microbial metabolites may affect prefrontal cortex neurotransmitter levels, leading to depressive episodes.…”
Section: Gut Microbiota and Metabolomicsmentioning
confidence: 99%
“…Besides being generally utilized as a protein building block, L-tyrosine is an amino acid precursor of norepinephrine and dopamine. Both norepinephrine and dopamine have an important role in the pathogenesis of depression [107].…”
Section: Mechanisms To Degrade the Uremic Precursors L-tyrosine/p-cresolmentioning
confidence: 99%